2019
DOI: 10.1002/open.201800282
|View full text |Cite
|
Sign up to set email alerts
|

A Series of Analogues to the AT2R Prototype Antagonist C38 Allow Fine Tuning of the Previously Reported Antagonist Binding Mode

Abstract: We here report on our continued studies of ligands binding to the promising drug target angiotensin II type 2 receptor (AT2R). Two series of compounds were synthesized and investigated. The first series explored the effects of adding small substituents to the phenyl ring of the known selective nonpeptide AT2R antagonist C38, generating small but significant shifts in AT2R affinity. One compound in the first series was equipotent to C38 and showed similar kinetic solubility, and stability in both human and mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
(152 reference statements)
0
6
0
Order By: Relevance
“…However, replacement with quinazolin-2-yl could restore the activity to the submicromolar level (compound 2), which indicated that the orientation of this bicyclic aromatic ring was important. We then switched to [5,6]-bicyclic heteroaromatic rings. Benzonimidazol-2-yl (compound 3) worsened the activity when compared to compound 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, replacement with quinazolin-2-yl could restore the activity to the submicromolar level (compound 2), which indicated that the orientation of this bicyclic aromatic ring was important. We then switched to [5,6]-bicyclic heteroaromatic rings. Benzonimidazol-2-yl (compound 3) worsened the activity when compared to compound 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…156,143 On the basis of docking data, a tentative model of the binding modes of ligand analogues compared to the prototype AT 2 R antagonist 26 was also proposed. 157 The differences in the predicted binding modes between agonists and antagonists in the active or inactive conformation of AT 2 R provide a possible explanation for the different biological behavior of the compounds.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…These compounds are thought to mimic the three C-terminal amino acids His-Pro-Phe of Ang II. Detailed molecular models explaining AT 2 R selectivity resulting from these minor structural changes, the relative position of the imidazole group and the isobutyl substituent on the thiophene ring of this series of nonpeptide ligands, provoking different functional activities and selectivity for the different conformations of the receptor, have been discussed in more detail at a molecular level, using modeling of AT 2 R in its active and inactive conformations. , On the basis of docking data, a tentative model of the binding modes of ligand analogues compared to the prototype AT 2 R antagonist 26 was also proposed . The differences in the predicted binding modes between agonists and antagonists in the active or inactive conformation of AT 2 R provide a possible explanation for the different biological behavior of the compounds.…”
Section: At2r Agonists or Antagonists As Therapeuticsmentioning
confidence: 99%
“…Similarly, the structure of compound 6 was aligned to sarile as co-crystallized to AT1R [43]. C21 was manually docked to AT2R based on the docking models of C21-derivatives generated in our lab [22,44].…”
Section: Docking and Molecular Dynamics (Md) Simulationsmentioning
confidence: 99%
“…Finally, the isobutyl group in this agonist scaffold is enclosed in a hydrophobic pocket formed by TM2, TM3, TM6, and TM7 (see Figure 6A), which is receptor-conformation specific thus connected to the agonist/antagonist the activity of the C21 derivatives. Indeed, this model was recently used in the course of our AT2R project to explain the SAR of a novel series of C21 derivatives as AT2R antagonists [44].…”
Section: Putative Binding Mode Of C21mentioning
confidence: 99%